From Traditional Public Administration To Digital Hybrid Public Administration - Şen, Alper Tunga (Zenodo, 2024)
When the process from past to present is examined, it can be seen that digitalization and technology are increasingly making themselves felt in daily life. This digitalization and technology not only causes many innovations in every field, but also causes many changes in the field of public administration. On the other hand, with the effects of this change, public administration is increasingly gaining a hybrid structure. Many different studies argue that the digital public management approach and the hybrid public management approach are different from each other. The purpose of this study is to reveal that the hybrid structure of today's public administration approach is actually realized together with digitalization. In addition, it is emphasized that today's public administration approach should actually be called a digital hybrid public administration approach. The study was carried out by the literature review method, and the works of many local and foreign scientists were examined. As a result, it is understood that today's public administration approach should be described as digital hybrid public administration. It is also important as it is a study that can be expanded with field research in the future.
Keywords: Public Administration; Hybrid; Digitalization; Technology; Finance and Investment (Other); Finans ve Yatırım (Diğer)